The financial situation of people with severe mental illness in an advanced welfare state - Marcus Eliason (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
Schizophrenia spectrum, bipolar, and major depressive disorders are severe mental illnesses (SMIs) that not only entail great suffering for those affected but also major societal costs. In this study, I use administrative register data to provide a detailed picture of the economic situation of people with SMI in Sweden during a period of ±10 years around first-time in-patient diagnosis. First-time in-patient diagnosis was associated with a considerable drop in earnings, which was largely compensated for by social transfers: mainly sickness and disability insurance. However, there were also large and increasing pre-diagnosis earnings gaps, relative to matched comparison groups, especially among those with schizophrenia spectrum disorders. This gap was to lesser extent compensated for by social transfers. Consequently, there was a permanent and increasing - due to lost earnings growth - income differential. Hence, findings in previous studies are confirmed: even in an advanced welfare state, people with SMI - especially those with schizophrenia - have an extremely weak position on the labour market and an equally difficult financial situation.
Keywords: I13; I14; J14; J65; 330; Schizophrenia spectrum disorder; bipolar disorder; major depressive disorder; social insurances; labour market situation